DIVING INTO SOCIETAL ISSUES: THE IMPACT OF DIGITAL ERA DEVELOPMENTS ON ENVIRONMENTAL ISSUES - Bekti Utomo (Adisam Publisher, 2024)
Environmental issues are a major threat to the survival of humans and other living creatures. In the digital era, the role of media in environmental ecology has become more complex. One way the media contributes to environmental ecology is by conveying information about environmental issues that require attention. Thanks to the media, many issues such as climate change, plastic pollution and sustainability are at the center of public attention. The media also plays an important role in exposing destructive practices that damage the environment, triggering responses from governments and civil society. Unraveling the ecological impact of media in the digital era is an important step in understanding the role of media in environmental conservation. The media has a great ability to shape our perceptions and actions towards environmental issues. This research investigates in depth the social content: the impact of the development of the digital era on environmental issues using a literature review approach. This research discusses the definition of environmental issues, the influence of technological developments in the digital era on people's lives, the ecological impact of digital media: the role in preserving the environment, technological developments in the digital era and environmental sustainability